1990
DOI: 10.1038/bjc.1990.141
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of collagen receptors in moderate and poorly differentiated colorectal adenocarcinomas

Abstract: Images Figure 1 Figure 2 Figure 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
2
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(60 citation statements)
references
References 16 publications
1
56
2
1
Order By: Relevance
“…Recent studies showed that patterns of integrin expression on tumour cells were different compared with normal counterparts and suggested that altered integrin expression may contribute to the invasive or metastatic phenotype. For example, the loss of integrin expression was reported in epithelial neoplasms, such as carcinomas of the breast, colon, pancreas and skin (Pignatelli et al, 1990;Zutter et al, 1990;Hall et al, 1991;Stamp and Pignatelli, 1991). On the other hand, up-regulation of aV#3 was described in malignant melanoma and glioblastoma multiforme, and acquisition of a4#1 has been described in malignant melanoma and renal cell carcinoma (Cheresh et al, 1989;Gladson and Cheresh, 1991;Tomita et al, 1995).…”
mentioning
confidence: 99%
“…Recent studies showed that patterns of integrin expression on tumour cells were different compared with normal counterparts and suggested that altered integrin expression may contribute to the invasive or metastatic phenotype. For example, the loss of integrin expression was reported in epithelial neoplasms, such as carcinomas of the breast, colon, pancreas and skin (Pignatelli et al, 1990;Zutter et al, 1990;Hall et al, 1991;Stamp and Pignatelli, 1991). On the other hand, up-regulation of aV#3 was described in malignant melanoma and glioblastoma multiforme, and acquisition of a4#1 has been described in malignant melanoma and renal cell carcinoma (Cheresh et al, 1989;Gladson and Cheresh, 1991;Tomita et al, 1995).…”
mentioning
confidence: 99%
“…There is overwhelming evidence that the normal function of both integrins and cds is critical in the induction and maintenance of cell differentiation in vitro (Pignatelli & Bodmer, 1888;Del Buono et al, 1991;Takeichi, 1988;Takeichi, 1991). It also appears that changes in their expression and/or function occur relatively frequently in transformed cells in vivo and this is associated with loss of differentiation and relates to the biological behaviour of tumour cells (Pignatelli & Bodmer, 1990;Pignatelli et al, 1990aPignatelli et al, , 1991Edelman et al, 1989;Shiozaki et al, 1991).…”
mentioning
confidence: 99%
“…Colorectal cancer is one of the commonest cancer in Western countries in which loss or down-regulation of both integrins (Pignatelli et al, 1990a) and E-cd (Edelman et al, 1989;Shiozaki et al, 1991) has been demonstrated immunohistochemically. Changes in both integrins and E-cd were found more frequently in poorly differentiated tumours in which the architecture and the glandular configuration were greatly impaired.…”
mentioning
confidence: 99%
“…To confirm the association of av with different /3 subunits and to determine whether this subunit also associated with /31 on (Pignatelli et al, 1990;Stallmach et al, 1992). The effect of a3 occupancy by fibronectin on tumour cell growth is not known.…”
Section: Immunoprecipitation Analysismentioning
confidence: 99%
“…A systematic study of integrin expression in normal colon, adenomas and carcinomas within the same patients has shown progressive loss of expression of 013, (which also recognises laminin and collagen) and a5#1, (which recognises fibronectin only) in the transition from adenomas to carcinomas (Pignatelli et al, 1990;Stallmach et al, 1992). In one report 75% of colorectal carcinomas were found to be completely negative for expression of the major VLA fibronectin receptor, CX5#I (Stallmach et al, 1992).…”
mentioning
confidence: 99%